Improving financial education and awareness on insurance and private pensions (OECD Publishing, 2008)
With public pensions under pressure and private pensions exposed to risk, individuals face an increasing variety of financial risks, particularly those linked to their retirement. This book analyzes the level of risk awareness of consumers and highlights good practices governments might initiate to enhance consumers' awareness and education on insurance and private pensions issues.--Publisher's description.